Facile Ball-Milling Synthesis of CuO/Biochar Nanocomposites for Efficient Removal of Reactive Red 120 - Wei, Xiaoqian; Wang, Xin; Gao, Bin; Zou, Weixin; Dong, Lin (ACS omega, 2020)
With the goal of improving the removal of anionic contaminants, copper oxide (CuO)-modified biochar (BC) nanocomposites were successfully prepared through simply ball milling CuO particles with BC. The physicochemical properties of the fabricated CuO/BC nanocomposites were systematically characterized by a series of techniques; their adsorption performances were assessed, and the main adsorption mechanism was revealed. X-ray powder diffraction, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy analyses of the nanocomposites showed the strong interaction between CuO and BC and confirmed the success of the ball-milling syntheses. Because of strong electrostatic attraction between the embedded CuO nanoparticles and reactive red (RR120), the composited adsorbents exhibited excellent RR120 removal. The 10%-CuO/BC nanocomposite achieved the best RR120 removal efficiency (46%), which is much higher than that of pristine BC (20%). In addition, the adsorption was insensitive to the change of solution initial pH (4–10). The 10%-CuO/BC also showed fast adsorption kinetics (equilibrium time < 3 h) and extremely high adsorption capacity (Langmuir maximum capacity of 1399 mg g–1) to RR120 in aqueous solutions. Findings from this study demonstrate not only the strong feasibility of ball-milling synthesis of BC-based nanocomposites but also the promising potential of the CuO/BC nanocomposites to remove aqueous anionic contaminants.